2018
DOI: 10.1002/jnr.24314
|View full text |Cite
|
Sign up to set email alerts
|

Interest of neuroimaging of social exclusion in suicide

Abstract: With one million deaths worldwide, suicide is a major health issue. The frequency of life events preceding suicidal act is high and raises the question of their role in suicidal process. At biological level, dysfunctional neural processing of social exclusion may participate in suicidal risk through an increased perception of social adversity in vulnerable subjects. The purpose of this narrative review is to discuss neuroimaging findings related to social exclusion and loneliness, and to open new perspectives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Studies over the last 20 years have increasingly showed a relation between emotional pain and physical pain ( 107–109 ). Work by Olie et al has specifically examined the increasing relevance of social exclusion to affective pain and suicide and further discussed the association between neuroimaging findings of social exclusion and suicide risk ( 110 ). They found that while the normal response to the affective pain of social exclusion increases activity in the anterior insula, ACC, and inferior OFC in normal controls, suicidal individuals show a decreased activation in these same regions, even compared with non-suicidal patients with a mood disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Studies over the last 20 years have increasingly showed a relation between emotional pain and physical pain ( 107–109 ). Work by Olie et al has specifically examined the increasing relevance of social exclusion to affective pain and suicide and further discussed the association between neuroimaging findings of social exclusion and suicide risk ( 110 ). They found that while the normal response to the affective pain of social exclusion increases activity in the anterior insula, ACC, and inferior OFC in normal controls, suicidal individuals show a decreased activation in these same regions, even compared with non-suicidal patients with a mood disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, although loneliness was a robust risk factor for suicide attempts, a latent factor of social connectedness, which included measures of social network size, attachment style, and perceived social support, did not emerge as significant predictors in the current investigation. One explanation for this finding could be that loneliness is associated with painful emotions (e.g., sadness, jealousy; Olié & Courtet, 2020), whereas the social connectedness measures reflect more disparate aspects of social support that are less reflective of perceived quality of social relationships and perceptions of social isolation and belongingness. Taken together, these findings suggest that loneliness may potentially have greater prognostic utility in predicting suicide attempts than previously conceptualized and thus warrants additional attention in future research, particularly in light of recent research from the COVID‐19 pandemic, which has demonstrated increasing rates of loneliness (Groarke et al, 2020; Hill et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Certain aspects of the neurobiological evidence for loneliness causing dementia remain unclear, and the research differs in its results in this context [7]. Loneliness affects different regions of the brain responsible for higher cognitive functions [46,[65][66][67][68][69][71][72][73][74][75][76]. Loneliness may affect the activation of orbitofrontal and prefrontal cortex leading to overactivation of HPA and, ultimately, atrophy of hippocampus-one of the most important structures in the development of dementia and AD [7,46,[65][66][67][68][69][70].…”
Section: Sociocognitive Skills and Neurobiologymentioning
confidence: 99%